2020
DOI: 10.4149/km_2019_1_113
|View full text |Cite
|
Sign up to set email alerts
|

Erosion wear evaluation of HVOF sprayed WC-12Co coating on some pipeline materials using Taguchi approach

Abstract: Pipeline materials used for the transportation of bottom ash slurry generally suffer from intense wear due to slurry erosion. In this work, High-Velocity Oxy-Fuel (HVOF) spray process was used for the deposition of WC-12Co coating on the Mild steel, SS 304 and SS 202. Slurry erosion pot tester was used for erosion tests of uncoated and coated materials. Effects of three factors namely slurry concentration, the speed of impacting particles and erosion test duration on erosion rate were investigated using the Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Poor abrasive wear behavior makes farmers less efficient and plays a major role in raising the cost of agriculture [2] by adversely affecting farmers' productivity, thereby making the whole process of agriculture economically unviable. Scientists and researchers have applied different techniques such as coatings [3][4][5][6][7][8][9][10][11][12][13][14], carburizing [15], nitriding and carbonitriding [15], boriding [15][16][17][18][19][20], and shot peening [21] to enhance the working life of rotavator blades. These techniques have shown promising results with regard to improving wear resistance in the short term, but limited data related to the long term success of these techniques is reported in the published work.…”
Section: Introductionmentioning
confidence: 99%
“…Poor abrasive wear behavior makes farmers less efficient and plays a major role in raising the cost of agriculture [2] by adversely affecting farmers' productivity, thereby making the whole process of agriculture economically unviable. Scientists and researchers have applied different techniques such as coatings [3][4][5][6][7][8][9][10][11][12][13][14], carburizing [15], nitriding and carbonitriding [15], boriding [15][16][17][18][19][20], and shot peening [21] to enhance the working life of rotavator blades. These techniques have shown promising results with regard to improving wear resistance in the short term, but limited data related to the long term success of these techniques is reported in the published work.…”
Section: Introductionmentioning
confidence: 99%
“…Żórawski [43] concluded that hardness obtained by WC-12CO coating done by HVOF spray process was 20% more as compared to the conventional coating. Singh et al [44] obtained significant improvement in hardness in case of WC-12CO coated material. Also, same coated material showed improvement in erosion wear resistance among all other substrates namely mild steel, SS304, SS202.…”
Section: Fig23 Wc-co Coating Used As a Magnetic Storage Unit [7]mentioning
confidence: 93%